THE WORD ‘HOW’ IN VICTOR E. FRANKL’S MAN’S SEARCH FOR MEANING AND ITS TRANSLATION - Sanang Hendriatma; Nugraha Krisdiyanta (Conscientia, 2021)
The word ‘how’ in Man’s Search for Meaning by Victor E. Frankl was translated into many words in Bahasa Indonesia. This research was aimed to know how the word ‘how’ translated into different words in Bahasa Indoneisa. The data were collected from English and Indonesian version books of Man’s Search for Meaning written by Victor E. Frankl. The researcher found there were 51 words ‘how’ which were translated into 9 types of words in Bahasa Indonesia and 10 words ‘how’ which were omitted. The result shows that there are 2 types of the word ‘how’, based on the function. They are as adverb of manner and as subordinating conjunction of noun clause. The function might cause why the word ‘how’ was translated into different types of words in Bahasa Indonesia. The translation of the word ‘how’ into Bahasa Indonesia was not only changing its word, but also considering the function of the word to produce the equivalence between the SL and the TL. In other words, the translation must consider the function of the word ‘how’ as well as its meaning.